IMPACTS OF STORED HUMAN URINE CONCENTRATION ON VEGETATIVE GROWTH OF TALINUM TRIANGULARE L. - Akporobaro, U.A.; Nwaka, R.N.; Agholor, O.; Chiedu, E.; Obiaigwe, J.A.; Akporobaro, E.P. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
This study evaluated the effect of 17-day stored human urine as an organic fertilizer on the vegetative growth of Talinum triangulare in Alihame Community, Nigeria. Three treatments consisting of stored human urine at 360.10 mL,620.10 mL, and a control (0 mL) were arranged in a completely randomized design (CRD) with three replicates. Data were collected on plant height, number of leaves, number of branches, and stem girth at 11, 18, 25, and 30 days after planting. Chlorophyll content, relative water content, and fresh biomass yield of leaves, and shoots were determined at harvest (30 days). The results showed that, stored human urine significantly improved all measured growth parameters compared with the control. The 620.10 mL treatment consistently produced the highest values for plant height, leaf number, stem girth, chlorophyll content, relative water content, and fresh biomass. The findings indicates that 17-day stored human urine can serve as an effective organic fertilizer for enhancing the growth and productivity of Talinum triangulare. Its utilization can contribute to sustainable soil fertility management and reduced dependence on synthetic fertilizers.